CANDIDA DIAGNOSTIC PLATFORMS: ESSENTIAL IN EARLY MANAGEMENT OF CANDIDA INFECTIONS (FUDMA JOURNAL OF SCIENCES, 2021)
Invasive candidiasis (IC) is associated with high morbidity and mortality. Candida species have significant roles in invasive candidiasis andthe emergence of clinical strains that are difficult to treat due tovirulent and resistant properties. Expansion of fungal pathogen diversity necessitates the development and adoption of new methods for prompt diagnosis and management. The review aimed to highlight the relevance of different Candida diagnostic methods for prompt management of Candida infections. The conventional gold standard diagnostic phenotypic-based (culture)method is time-consuming, associated withlow specificity and subjective interpretation.The specificity and sensitivity performances for candidaemia or deep-seated candidiasis of biochemical-based methods, including VITEK, API 20C AUX, and latex agglutination, have higher resolution than the culture. Nucleic acid-basedpolymerase chain reaction diagnostic techniques have been rapidly evolving. PCR will improve the diagnostic performance and patient outcome. The PCR technique uses different ribosomal DNA gene complexes, including D1/D2, ITS1/ITS4, or IGS1/IGS2, ashelpful markersto delineate the main pathogenic fungal species belonging to different genera. Sensitive and specific diagnostic methods for Candida speciesare significant for clinical decision and effective clinical outcome.
Keywords: Invasive candidiasis; diagnosis; culture; PCR; biochemical methods